2004
DOI: 10.1007/s11176-005-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and steric structure of 2-[1-(3-chlorophenyl)-2,2,2-trifluoroethoxy]-3-(trichloromethyl)-6,7-benzo-1,4,2λ5-dioxaphosphepin-5-one 2-oxide

Abstract: The reaction with chloral of 2-[1-(3-chlorophenyl)-2,2,2-trifluoroethoxy]-5,6-benzo-1,3,2-dioxaphosphorinan-4-one containing a chiral fluorinated exocyclic substituent on phosphorus leads to formation of 2-[1-(3-chlorophenyl)-2,2,2-trifluoroethoxy]-3-(trichloromethyl)-6,7-benzo-1,4,2l 5 -dioxaphosphepin-5-one 2-oxide with a high regio-and stereoselectivity. The molecular and supramolecular structure of the isolated diastereomer was established by means of X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The title compound displays three intramolecular C-H•••O hydrogen interactions, similar to that found in polyfluorinated dioxaphosphepinone oxide derivatives (Gubaidullin et al, 2004). These hydrogen bonds display an S(6) graph-set motif (Bernstein et al, 1995)…”
Section: All Bond Lengths In (I)mentioning
confidence: 59%
See 2 more Smart Citations
“…The title compound displays three intramolecular C-H•••O hydrogen interactions, similar to that found in polyfluorinated dioxaphosphepinone oxide derivatives (Gubaidullin et al, 2004). These hydrogen bonds display an S(6) graph-set motif (Bernstein et al, 1995)…”
Section: All Bond Lengths In (I)mentioning
confidence: 59%
“…For related literature, see: Allen et al (1987); Dakternieks et al (1978); Gubaidullin et al (2004); Halper & Cohen (2005); Hanes et al (2002); Robinson et al (1971); Smart (2001); Timperley & White (2003); Timperley et al (2000); Bernstein et al (1995); Larson (1970); Prince (1982); Watkin (1994).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They are capable of being involved in cascade reactions with activated carbonyl compounds, Schiff bases, and ylidene derivatives of dicarbonyl compounds. In these reactions, the carbonyl group can participate in one or another step of the cascade process, leading to the formation of 1,3,2-dioxa(oxaza)-and 1,4,2-dioxa-(oxaza)phosphepines, 1,2-oxaphospholanes, and other difficultly accessible compounds [5][6][7][8][9][10][11][12].We recently showed that cyclic phosphorus(III) derivatives having an activated carbonyl group in the γ-position with respect to the phosphorus atom, e.g., 2-phenyl-4,4-bis(trifluoromethyl)-4,5-dihydro-1,3,2-benzodioxaphosphepin-5-one (I), also undergo cascade transformations by the action of trichloroacetaldehyde and hexafluoroacetone. As a result, cage-like propeller phosphorane with a phosphorus-carbon bond (structure II) [13,14] or spiran structure III is formed; in the latter structure, the γ-carbonyl carbon atom becomes a spiro atom [15] (Scheme 1).…”
mentioning
confidence: 99%
“…They are capable of being involved in cascade reactions with activated carbonyl compounds, Schiff bases, and ylidene derivatives of dicarbonyl compounds. In these reactions, the carbonyl group can participate in one or another step of the cascade process, leading to the formation of 1,3,2-dioxa(oxaza)-and 1,4,2-dioxa-(oxaza)phosphepines, 1,2-oxaphospholanes, and other difficultly accessible compounds [5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%